Reference and information services : an introduction - Cassell, Kay Ann; Hiremath, Uma (Facet, 2013)
This fully updated edition of the landmark textbook by Cassell and Hiremath is designed to complement every introductory library reference course and is the perfect text for students and librarians looking to expand their personal reference knowledge